2001
DOI: 10.1016/s0896-6273(01)00182-9
|View full text |Cite
|
Sign up to set email alerts
|

Forward Signaling Mediated by Ephrin-B3 Prevents Contralateral Corticospinal Axons from Recrossing the Spinal Cord Midline

Abstract: To investigate Eph-ephrin bidirectional signaling, a series of mutations were generated in the ephrin-B3 locus. The absence of both forward and reverse signaling resulted in mice with mirror movements as typified by a hopping locomotion. The corticospinal tract was defective as axons failed to respect the midline boundary of the spinal cord and bilaterally innervated both contralateral and ipsilateral motor neuron populations. A second mutation that expresses a truncated ephrin-B3 protein lacking its cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
184
2
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(206 citation statements)
references
References 52 publications
17
184
2
3
Order By: Relevance
“…Ephrin-B3͞LacZ mice, encoding a chimeric protein with a ␤-gal moiety replacing the intracellular segment of ephrin-B3, and ephrin-B3 knockout mice are described in Yokoyama et al (12). EphA4͞LacZ mice, carrying a LacZ cDNA in place of a functional EphA4 allele, were provided by P. Charnay (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ephrin-B3͞LacZ mice, encoding a chimeric protein with a ␤-gal moiety replacing the intracellular segment of ephrin-B3, and ephrin-B3 knockout mice are described in Yokoyama et al (12). EphA4͞LacZ mice, carrying a LacZ cDNA in place of a functional EphA4 allele, were provided by P. Charnay (15).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic ablation of ephrin-B3 in mice thus results in bilateral innervation by the CST and a kangaroo-like ''hopping'' phenotype. Knocking out EphA4 produces an identical phenotype, demonstrating a receptor͞ligand Eph͞ephrin relationship in this process (12).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Such studies are particularly relevant in mammalian systems where it has been an immense task to characterize the principle constituents of neural networks from both developmental genetics (1) and physiological (10)(11)(12) perspectives. A recent example of a genetic loss-of-function that is related to a distinct abnormal behavioral phenotype is the rabbit-like hopping gait exhibited in mice that have a targeted deletion of the axon guidance molecules EphA4 and ephrinB3 (13)(14)(15). This pronounced phenotype could be reproduced in isolated spinal cords from mutant mice, suggesting that the neuronal network controlling locomotion, also called the central pattern generator (CPG), is genetically reconfigured in the mutants (16).…”
mentioning
confidence: 99%
“…During corticospinal tract development, Ephrin-B3 is concentrated at the spinal cord midline and prevents EphA4-expressing axon collaterals of the corticospinal tract from re-crossing the midline since they have already crossed once at the spinomedullary junction (Davy and Soriano, 2005). CST axons in either Ephrin-B3 or EphA4 mutant mice exhibit bilateral innervation of spinal grey matter due to the loss of the midline barrier (Ephrin-B3) or the receptor to sense the barrier (EphA4) (Dottori et al, 1998;Kullander et al, 2001;Yokoyama et al, 2001). Benson et al reported the expression of Ephrin-B3 in postnatal myelinating oligodendrocytes in the mouse spinal cord and provided evidence that this myelin component confers sensitivity to postnatal cortical neurons that express EphA4 (Benson et al, 2005).…”
Section: Axon Guidance Molecules: Potential New Roles For Old Moleculesmentioning
confidence: 99%